Infantile Feeding Difficulties - Laura C. McCarthy DO; Venkedesh Raju MD, FAAP; Bhavana S. Kandikattu MD, FAAP; Craig S. Mitchell DO (SAGE Publishing, 2014)
Background . Gastric volvulus refers to a torsion of all or part of the stomach that may cause an obstruction of the foregut. The clinical symptoms of gastric volvulus range from asymptomatic to life-threatening and thus must be rapidly diagnosed. However, the presenting symptoms of gastric volvulus vary widely, which may cause diagnosis to be delayed or missed. Objective . Describe varying presentations of gastric volvulus (including a case report of a rare presentation), pathophysiology of the entity, and how to diagnose/treat the phenomenon. Design/Method . Article review and case presentation. Results . Our patient was taken to the operating room for a gastropexy and G-tube placement. During surgery, the stomach was redundant and large, but not currently torsed, consistent with intermittent organoaxial volvulus. There are several approaches to classifying gastric volvulus as well as different theories on how to treat the volvulus based on type and degree of rotation that this article aims to detail more thoroughly. Conclusion . There are a growing number of case reports describing gastric volvulus, which had historically been viewed as a rare finding. The presenting symptoms of gastric volvulus commonly mimic other, more benign newborn diagnoses, and thus can be difficult to diagnose. We present our patient as well as an article review of other cases to highlight the diverse presentations of gastric volvulus so this potentially devastating disease can be diagnosed quickly with prompt treatment initiation.